2014
DOI: 10.1108/nfs-06-2013-0072
|View full text |Cite
|
Sign up to set email alerts
|

Babul (Acacia nilotica)

Abstract: Purpose – The prevalence of diabetes has increased manifold and now become a public health problem from being mild disorder. There is a need to discover more effective and safer antidiabetic agents by utilizing the rich heritage of medicinal plants. Tannins are polyphenols that are obtained from various parts of different plants belonging to multiple species and considered as potential drugs for the treatment of non-insulin-dependent diabetes mellitus. The paper aims to discuss these issues. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…In the present study, phytochemical screening showed the presence of triterpenes, flavonoids, phenols, and tannins compounds within the extract of H. sabdariffa. Several studies have demonstrated the involvement of phytochemical compounds such as triterpenes [31,32], flavonoids [33][34][35], and tannins [36] for the management of diabetes. These compounds might act by several mechanisms such as enhancing insulin secretion [37] or regenerating insulinproducing pancreatic β-cell population in the islets of Langerhans [38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, phytochemical screening showed the presence of triterpenes, flavonoids, phenols, and tannins compounds within the extract of H. sabdariffa. Several studies have demonstrated the involvement of phytochemical compounds such as triterpenes [31,32], flavonoids [33][34][35], and tannins [36] for the management of diabetes. These compounds might act by several mechanisms such as enhancing insulin secretion [37] or regenerating insulinproducing pancreatic β-cell population in the islets of Langerhans [38][39][40].…”
Section: Discussionmentioning
confidence: 99%